2022
DOI: 10.1111/tpj.15858
|View full text |Cite
|
Sign up to set email alerts
|

A chromosome‐level genome of Syringa oblata provides new insights into chromosome formation in Oleaceae and evolutionary history of lilacs

Abstract: Lilacs (Syringa L.), a group of well-known ornamental and aromatic woody plants, have long been used for gardening, essential oils and medicine purposes in East Asia and Europe. The lack of knowledge about the complete genome of Syringa not only hampers effort to better understand its evolutionary history, but also prevents genome-based functional gene mining that can help in the variety improvement and medicine development. Here, a chromosome-level genome of Syringa oblata is presented, which has a size of 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…For example, Forsythia originated in eastern China 16.6 Ma ago, then dispersed westward during the Late Miocene eventually reaching Europe (Ha et al., 2018); Syringa originated in northeastern China about 14.73 Ma ago. Five main groups of the genus were formed about 9.97 Ma ago and spread in several directions including toward Japan, Central Asia, and Europe (Wang, Lu, et al., 2022). Considering the fruit type of the Oleaceae i.e.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Forsythia originated in eastern China 16.6 Ma ago, then dispersed westward during the Late Miocene eventually reaching Europe (Ha et al., 2018); Syringa originated in northeastern China about 14.73 Ma ago. Five main groups of the genus were formed about 9.97 Ma ago and spread in several directions including toward Japan, Central Asia, and Europe (Wang, Lu, et al., 2022). Considering the fruit type of the Oleaceae i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the structure, plant floral volatiles can be divided into three main groups: terpenoids, phenylpropanoids/benzenoids and fatty acids ( Muhlemann et al., 2014 ), and previous studies indicated that terpenes were the main components of S. oblata volatiles ( Li et al., 2006 ; Gegen et al., 2022 ; Wang et al., 2022 ). Lilac aldehyde and lilac alcohol were the main volatiles of the S. oblata flowers found in our study which were oxygenated derivatives of the monoterpenoid linalool ( Kreck et al., 2003 ; Boachon et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…S. oblata has a strong floral fragrance, and previous studies have revealed that the main volatiles of its flowers are terpenoids such as lilac aldehyde, lilac alcohol, α-pinene, sabinene and β-pinene ( Li et al., 2006 ; Gegen et al., 2022 ; Wang et al., 2022 ), while terpene synthase (TPS) is the pivotal gene family for the biosynthesis of plant terpenes ( Chen et al., 2011 ). Plant secondary metabolites usually require post-modification processes to produce biologically active metabolites ( Li et al, 2009 ) and many S. oblata flower volatiles undergo post-modification processes, such as lilac aldehyde and lilac alcohol, which are oxygenated derivatives of linalool formed through the catalysis of cytochrome P450 ( Raguso, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…It's native to Southwest China and widely distributed in Southwest China, North China, and the middle latitudes of Eurasia and North America. [1] Besides its high ornamental value, SO has been used in both traditional Chinese medicine (TCM) and Mongolian folk medicine (MFM). According to the theory of Chinese medicine, the medicinal parts of SO include the leaves, buds, flowers, branches, and bark, which have been used to treat hepatitis, intestinal disorders, and diarrhea, whereas the heartwood of SO is used as an MFM for its efficacy of clearing heat and inhibiting the partial prosperity of "Khii" in the theory of traditional Mongolian medicine.…”
Section: Introductionmentioning
confidence: 99%
“…(SO), also known as lilac, is a well‐known deciduous shrub belonging to the Oleaceae family. It's native to Southwest China and widely distributed in Southwest China, North China, and the middle latitudes of Eurasia and North America [1] . Besides its high ornamental value, SO has been used in both traditional Chinese medicine (TCM) and Mongolian folk medicine (MFM).…”
Section: Introductionmentioning
confidence: 99%